Compact Substrate Integrated Wireless Cure Monitoring Sensor for Epoxy Resin - Groh, Jannis; Lee, William; Schür, Jan; Distler, Felix; Vossiek, Martin (48th European Microwave Conference (EuMW 2018), 2018)

Complex Permittivity Measurements of Curing Epoxy Resin in Glass Fibre Reinforced Composite - Groh, Jannis; Lipka, Melanie; Schür, Jan; Vossiek, Martin (46th European Microwave Conference, 2017)

Design, Calibration and Validation of 24 GHz Resonators for Epoxy Resin Cure Monitoring Systems in the Fibre-Reinforced Plastics Fabrication - Groh, Jannis; Schür, Jan; Javdanithehran, Mehdi; Ziegmann, Gerhard; Vossiek, Martin (Proc. 19th World Conference on Non-Destructive Testing, 2016)
lhft_intern.bib::Groh2016a

Effect of embedded printed circuit board (PCB) sensors on the mechanical behavior of glass fiber-reinforced polymer (GFRP) structures - Javdanitehran, Mehdi; Hoffmann, R.; Groh, Jannis; Vossiek, Martin; Ziegmann, G. (Smart Materials and Structures, 2016)
The embedding of dielectric chipless sensors for cure monitoring into fiber-reinforced thermosets allows for monitoring and controlling the curing process and consequently higher quality in production. The embedded sensors remain after the processing in the structure. This affects the integrity of the composite structure locally. In order to investigate these effects on the mechanical behavior of the glass fiber-reinforced polymer (GFRP), sensors made on special low loss substrates are integrated into laminates with different lay-ups and thicknesses using vacuum assisted resin transfer molding (VARTM) method. In a parametric study the size of the sensor is varied to observe its influence on the strength and the stiffness of the laminates according to its lay-up and thickness. The size and orientation of the resin rich areas near sensors as well as the distortion in load bearing area as the consequences of the introduction of the sensors are investigated in conjunction with the strength of the structure. An empirical model is proposed by the authors which involves the previously mentioned factors and is used as a rapid tool for the prediction of the changes in bending and tensile strength of simple structures with embedded sensors. The methodology for model's calibration as well as the validation of the model against the experimental data of different laminates with distinct lay-ups and thicknesses are presented in this work. Mechanical tests under tensile and bending loading indicate that the reduction of the structure's strength due to sensor integration can be attributed to the size and the orientation of rich resin zones and depends over and above on the size of distorted load bearing area. Depending on the sensor's elastic modulus the stiffness of the structure may vary through the introduction of a sensor.
Keywords: analytical modelling; embedded sensor; glass fibres; mechanical properties

Effects of Different Types of Burn Wounds and its Dressings on Millimeter-Wave Images - Oppelt, Daniel; Korf, Patrick; Adametz, Julian; Groh, Jannis; Vossiek, Martin; Zhuravleva, Kristina; Goertz, Ole (Frequenz, 2018)

Innovative drahtlose Sensorkonzepte für das in-situ Monitoring von Aushärtevorgängen in Epoxidharzsystemen und Faserverbundbauteilen - Dorbath, Benedikt; Groh, Jannis; Schür, Jan; Vossiek, Martin (4. Symposium Materialtechnik, 2021)

Large-Signal RF Circuit Model for a High-Power Laser Diode Module - Engelbrecht, Rainer; Groh, Jannis; Stumpf, Christopher; Adametz, Julian; Schmauß, Bernhard (IEEE Photonics Technology Letters, 2014)
An electrical large-signal circuit model for a 30-W high-power laser diode module is presented. Such modules are designed primarily for continuous wave (cw) operation but can be pulsed in the sub-μs temporal range for special applications. Our model is thus valid up to 20 MHz in the electrical frequency domain. The elements of the circuit model have been derived from RF impedance measurements using a calibrated vector network analyzer and a high-current dc/RF bias-T. The impedance is dominated by the inductance of the high-current connecting leads from the laser driver to the laser chip. The skin effect has been found to influence considerably both resistive and inductive impedances at high frequencies. For large-signal circuit simulations in the time domain, the current-voltage characteristic of the diode p-n junction is included by an analytic equation. The model is verified by comparison of simulation results with measured currents, voltages, and laser powers in large-signal pulsed-mode operation. This model is well suited for the design of optimized pulsed-current driver circuits. © 1989-2012 IEEE.
UnivIS-Import:2015-03-09:Pub.2014.tech.IE.LEH.larges
Keywords: Circuit modeling; Equivalent circuits; High-power laser diode; Impedance measurement; Large-signal; Optical pulses; Parameter extraction; Radio-frequency; Simulation

Mikrowellenbasiertes Prozessmonitoring von Aushärtungsvorgängen bei der Herstellung von GFK-Bauteilen - Groh, Jannis; Javdanitehran, M; Vossiek, Martin; Javdanitehran, Mehdi (3. Fachseminar Mikrowellen- und Terahertz-Prueftechnik in der Praxis, 2017)

MIMO-SAR Based Millimeter-Wave Imaging for Contactless Assessment of Burned Skin - Oppelt, Daniel; Adametz, Julian; Groh, Jannis; Goertz, Ole; Vossiek, Martin (International Microwave Symposium (IMS2017), 2017)

Multifunktionales Sensorsystem fuer Prozessueberwachung in Faserverbundwerkstoffen - Javdanitehran, M; Groh, Jannis (Workshop Mikroproduktion von Materialhybriden, 2015)
lhft_intern.bib::Groh2015

Wireless Chipless Cure Monitoring Sensor for Fibre Reinforced Plastics - Groh, Jannis; Lipka, Melanie; Schür, Jan; Vossiek, Martin (International Microwave Symposium (IMS2017), 2017)